Doktrin Baptisan Roh Kudus Martyn Lloyd-Jones Berdasarkan Sudut Pandang Teologi Reformed - Runggang, Yohanis; Ongkowidjojo, Hendry (Verbum Christi: Jurnal Teologi Reformed Injili, 2024)
The doctrine of baptism with the Holy Spirit remains a subject of theological debate, which has not yet reached a consensus among scholars within the Church traditions. These differences are not only found across church traditions but also within Reformed theology itself, as reflected in the views of Martyn Lloyd-Jones. This article examines and evaluates the main aspects of Lloyd-Jones' thought using the Reformed view as a primary framework. This analysis finds ambiguity in Lloyd-Jones' understanding of the baptism with the Holy Spirit. Although there are differences, Lloyd-Jones's views remain part of the broader Reformed view.